Comparison of an X4-AUV Performance Using A Direct Lyapunov - PD Controller and Backstepping Approach - Zainah, Md. Zain; Nur Fadzillah, Harun; Keigo, Watanabe; Isaku, Nagai (Engineering and Technology Publishing, 2015)
An X4-AUV is nonlinear, coupled and unstable system. In this paper, we present the results of two control schemes applied to an X4-AUV. A direct use of Lyapunov control theory and PD controller technique and backstepping technique have been applied to stabilize the system. We performed the simulations to see the comparative performance result of an X4-AUV under two control schemes.